Evaluation of empirical antibiotic treatment in culture negative pyogenic vertebral osteomyelitis - Doğan, Mustafa; Şimşek, Abdullah Talha; Yılmaz, İbrahim; Karaarslan, Numan (Turkish Neurosurgical Society, 2019)
AIM: To investigate the efficacy of empirical antibiotic treatment in culture-negative pyogenic vertebral osteomyelitis (PVO) cases. MATERIAL and METHODS: The records of patients with culture-negative PVO who were treated at infectious diseases and neurosurgery outpatient clinics in the past four years were examined retrospectively. The control group comprised healthy subjects with similar age, gender, and body mass index but without pathology. The comparison of the groups was performed by analysis of variance. Statistical significance was accepted as p < 0.05. RESULTS: No statistically significant difference in the white blood cell count and erythrocyte sedimentation rate was found between the spondylodiscitis and the healthy subject groups when the blood parameters obtained before and after the treatment (p > 0.05). However, a statistical significance was assessed in the results of the comparison for C-reactive protein (p < 0.05). CONCLUSION: In the context of evidence-based medicine and the rational use of antibiotics, it is clear that antibiotics should be preferred according to the culture antibiogram results in the treatment of infectious diseases.
Keywords: Empirical Treatment; Pyogenic Vertebral Osteomyelitis; Rational Antibiotic Use; Rational Drug Use; Spondylodiscitis